The Effect of Anticipation Guide Strategy in Teaching Reading - Vivin Krismawanti Modjanggo (Sintuwu Maroso Journal of English Teaching, 2019)
This research aims at finding the effect of anticipation guide strategy in teaching reading to the students of the English Education Study Program at Unsimar Poso.  This is quantitative research and the researcher uses a pre-experimental research design. The samples of this research are students who enrolled in Reading 1 class in 2018/2019.  In conducting the research, the researcher conducts the pre-test before the treatment and the post-test after the treatment. Based on the result of the research, it is shown that anticipation guide strategy can affect students’ of Reading Class comprehension at FKIP UnsimarPoso. It could be seen from the result of data analysis in which students’ mean score in the pre-test is increased from 55.6 to 89 on the post-test. The result of t-counted (17.6) is higher than the result of the t-table (1.713). Therefore, it can be said that the use of anticipation guide strategy can affect the students’ of Reading 1 class at FKIP UnsimarPoso